2012
DOI: 10.1021/jp211598m
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Luminescent Properties of HfO2:Eu Powders with Li, Ta, Nb, and V Codopants

Abstract: Monoclinic HfO 2 :Eu,M (M = Li, Ta, Nb, V) powders were prepared with the Pechini method. The M-dopants were added for charge compensation of Eu 3+ positioned in Hf (IV) site. This was hoped to enhance the host-to-activator energy transfer and consequently the overall efficiency of X-ray excited luminescence. Only in the case of codoping with Nb, the final phosphor did not contained any foreign phases indicating that (Eu 3+ ,Nb (V) ) pairs easily dissolved in the host. In the HfO 2 :Eu,V composition, the phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…The origin of these structural modifications are attributed to the charge mismatch at the doping lattice site, and the consequent creation of defects by the substitutional doping. One proposed approach to avoid the effect of this defective dopant implies the simultaneous doping with elements with higher oxidation state than hafnium or zirconium, in order to compensate for the charge mismatch induced by the substitution of Hf 4+ or Zr 4+ by only trivalent RE 3+ ions [2,7,9,11,12]. This strategy was successfully applied to hafnia and zirconia by using Nb 5+ or Ta 5+ as co-dopants and a significant improvement of the Eu 3+ related emission was reported with increase ranging from 5 to 50 times [2,7,12].…”
Section: Introductionmentioning
confidence: 99%
“…The origin of these structural modifications are attributed to the charge mismatch at the doping lattice site, and the consequent creation of defects by the substitutional doping. One proposed approach to avoid the effect of this defective dopant implies the simultaneous doping with elements with higher oxidation state than hafnium or zirconium, in order to compensate for the charge mismatch induced by the substitution of Hf 4+ or Zr 4+ by only trivalent RE 3+ ions [2,7,9,11,12]. This strategy was successfully applied to hafnia and zirconia by using Nb 5+ or Ta 5+ as co-dopants and a significant improvement of the Eu 3+ related emission was reported with increase ranging from 5 to 50 times [2,7,12].…”
Section: Introductionmentioning
confidence: 99%
“…The phonon losses of the host glass are also reported to have been reduced due to the addition of HfO 2 [22]. In some other studies on HfO 2 mixed glasses, it was found that these glasses are efficient absorbers of the incident gamma/X-rays [23,24]. In view of such special characteristics, HfO 2 containing glasses are being used as optical coatings for astronomical charge coupled, devices, IR optical devices, antireflective multi-layer coatings for night vision devices and for the applications in the inorganic scintillators [25e27].…”
Section: Introductionmentioning
confidence: 91%
“…10 Though much less studied than the ZrO 2 homologue, several reports evidenced remarkable photoluminescence (PL) and scintillator properties of monoclinic and tetragonal/cubic phases of HfO 2 when doped with lanthanide (Ln) ions such as Ce, Sm, Eu, Tb, and Dy. 57,1215 As Zr and Hf are regarded as the two chemically most similar homogenesis elements, 16 HfO 2 and ZrO 2 are called twin oxides 17,18 because of their similar crystal structure, with close ionic radii of 0.78 Å (Hf 4+ ) and 0.79 Å (Zr 4+ ), 19 despite their large difference in the atomic number, Z, 72 to 40, respectively. In the bulk, hafnia and zirconia can each adopt three different, albeit related, crystal structures at ambient pressures, that is, monoclinic, tetragonal, and cubic.…”
Section: Introductionmentioning
confidence: 99%